Active medulloblastoma enhancers reveal subgroup-specific cellular origins - Lin, Charles Y.; Zapatka, Marc; Jones, Barbara Christine; Jones, David T. W.; Kool, Marcel; Buchhalter, Ivo; Johann, Pascal-David; Chavez, Lukas; Gröschel, Stefan; Eils, Roland; Lichter, Peter; Pfister, Stefan; et al. (Nature, 2016)
Genomic studies of the paediatric brain tumour medulloblastoma have revealed four clinically distinct molecular subgroups. In this study, the authors map active gene regulatory elements in 28 primary medulloblastoma tissues to reveal differentially regulated enhancers across the different subgroups. The results allow insight into the transcription factors that characterize subgroup divergence and the cellular origin of the poorly characterized Group 3 and 4 subgroups.